Австрийская региональная литература ХХ в.: генезис феномена провинция - Isapchuk, Yulia (Лингва Ереван, 2019)
The study analyzes the main formation’s phases of the Austrian Regional literature (Heimatliteratur) in the 20th century. The investigation stresses the similar and distinctive features of the „Heimatkunst” in Germany and „Provinzkunst” in the Habsburg Monarchy, where the name of the last term emphasizes the fundamental spatial orientation and detachment from the culture of big cities in addition. The changes in the direction’s connotation in the context of the socio-political development of the country in the 1930–40s are underlined. The cultural tradition of Regional art after the Second World War is highlighted. The attention is drawn to the most common genre (Regional novel), which evolves into the Antiregional literature and prevails in the Austrian discourse of the 1960-80s.
20TH CENTURY AUSTRIAN REGIONAL LITERATURE: THE GENESIS OF THE PHENOMENON OF PROVINCE
Keywords: Austrian literature; Regional literature (Heimatliteratur); „Heimatkunst”; „Provinzkunst”; province; Regional novel (Heimatroman)